Works councils and organizational gender policies in Germany - Uwe Jirjahn; Jens Mohrenweiser (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2019)
While education and labor force participation of women have been increased, there is still a substantial gender gap in labor market opportunities. This gives rise to the question of what factors lead employers to promote work-family balance and gender equality. We address this question by examining the influence of works councils on the gender policies of establishments in Germany. Using data of the IAB Establishment Panel, we find that the incidence of a works council is associated with an increased likelihood that an establishment provides family-friendly practices and promotes equal opportunities of men and women. This finding also holds in a recursive multivariate probit model that accounts for potential endogeneity of works council incidence.
Keywords: J13; J16; J52; J53; 330; Non-union employee representation; works councils; gender equality; workfamily balance; equal opportunities; organizational gender policies